ATUAÇÃO DA FISIOTERAPIA EM UMA UNIDADE DE SAÚDE DA FAMÍLIA: RELATO DE UMA EXPERIÊNCIA ACADÊMICA - LASTA, ANDRE; PFEIFER, DAIANE; BERLEZI, EVELISE; MÖHLER, MARISA; STRASSBURGER, MÁRCIO; VARGAS, PRISCILA; SILVA, TICIANE C. E. (Salão do Conhecimento, 2013)
Resumo